Education Inputs In Uganda : An Analysis of Factors Influencing Learning Achievement in Grade Six - Nannyonjo, Harriet (Washington, DC: World Bank, 2012)
This study on effective use of school inputs in Uganda is intended to contribute to the policy debate on how to make the best use of available resources to improve learning outcomes. It comes at an opportune time in Uganda when there are increasing demands on the education budget, yet it is unlikely that substantial increases in the sector budget envelope will be provided given other competing national priorities, as well as the need for additional resources to finance post primary education and training. This report emphasizes: the need for a balanced focus on resource availability and use, because without appropriate use or management, resources may not lead to improved learning; helping teachers to effectively teach large classes; and the importance of investing more in in-service training focused on pedagogical practices than on training teachers to acquire academic qualifications. The study also points to the need to examine and include teacher effectiveness as key criteria for determining teacher remuneration. With regard to automatic promotion, this study, and indeed the general literature suggest that repetition tends not to work within the same context and the same teaching styles. The findings of this study clearly demonstrate the need to focus on school and classroom processes and better use of education resources focused on improvement of learning.